PENGARUH KOMBINASI DAN ARAS REMPAH DALAM RANSUM TERHADAP KINERJA PUYUH JANTAN - FX Suwarta; CH. Lilis Suryani (Universitas Muhammadiyah Semarang, 2015)
The research were to study the effect of combination and spices level on the ration on quail male performance. The study was conducted with a random design factorial (3x4x3) with the combination treatment factors spices (3) is Turmeric (K) and cinnamon (KM) in the ratio 25:75%; 50:50% and 75:25% and the level of use of spices (4) i.e 0; 0.5%; 1 and 1.5%. Each combination treatment was repeated three replication., using 40 quails. Quail reared from the age of 1 day to 28 days.Rations were given aproach isonutriens only distinguishable combinations and level spice suplementation. The variables measured were of performance i.e feed intake, body weight, feed conversion ratio and carrcass weight. Data were analyzed variance followed Duncan Multiple Range Test. The results showed the use of a combination of Turmeric and Cinnamon improve feed intake and body weight significantly and improve feed conversion and carcass weight. The use of spice to 1.5% in the ration able to improve feed intake, body weight, feed conversion and carcass weight. There is interaction between the level and combinationa of spces for all variables. The best combination of spices obtained on the use of spices by comparison Turmeric: 50% and cinnamon 50% with a 1% level suplementation.Keywords : quail, spices, performance